Country a novel - Steel, Danielle (New York Delacorte Press, 2015)
Life for Stephanie Adams is all about being a devoted mother. For years, she has kept her unhappy marriage a secret, intent on protecting her children from seeing their family break up. Then Stephanie's husband dies suddenly, and she sees a chance for everything to be different. Stephanie strives to balance her children's grief with her desire to move on from the past -- but after years of giving up her life for everyone else, what should she do next? A spur-of-the-moment road trip leads her to Las Vegas, the Grand Canyon, and a chance meeting ... and her whole life changes forever. When Stephanie meets country music megastar Chase Taylor, he opens up his exciting world to her. In Nashville, the music is bittersweet and the lyrics true. Now, Stephanie is no longer the same woman. By seizing the day, she has found a way to be free and happy. But can her family find it in their hearts to let her go?
1
Keywords: Country musicians -- Tennessee -- Nashville -- Fiction; Man-woman relationships -- Fiction; Widows -- California -- San Francisco -- Fiction; Love stories